Gamma Variate Analysis of Pulmonary Dilution Curves for Quantitation of Left-to-Right Cardiac Shunts - Olkkonen, H. (Nuklearmedizin - NuclearMedicine, 1978)
Left-to-right cardiac shunts were quantified in patients with atrial septal defect using a gamma variate least squares fit to radionuclide pulmonary dilution curves. All patients were studied with cardiac catheterization. There was a close correlation between the Fp/Fs ratios obtained by oximetry in cardiac catheterization and by gamma variate analysis. The results suggest that the radionuclide dilution method is sufficiently reliable to be used as a screening test for the detection and quantitation of left-to-right cardiac shunts.